The Personal is Not Political: At Least in the UK's Top Politics and IR Departments. (November 2013) - Foster, Emma; Kerr, Peter; Hopkins, Anthony; Byrne, Christopher; Ahall, Linda
Through mapping the provision of teaching gender and sexuality studies on politics/political science and international relations (IR) programmes, this article asserts that the top-ranked politics and IR departments in the UK offer very little provision of such teaching. We argue that this lack of gender and, more so, sexuality teaching is highly problematic for the discipline. Moreover, we suggest that the lack of such provision is not reflective of staff research interests, potentially not reflective of the market (i.e. students), works against the trend of mainstreaming gender, and is problematic in the wider sense in that gender and sexuality are rendered invisible or as trivial matters. Overall, then, this article contends that curricula in politics and IR departments work to perpetuate the idea that the 'personal is not political', thereby defining the parameters of the discipline in both a narrow and inaccurate way.